Simanihot: um modelo de simulação da cultura da mandioca e sua aplicação em clima futuro no Rio Grande do Sul - Tironi, Luana Fernandes (2016)
Crop models are tools that can help to assist in decision making on crops management and also in studies of the impact of future climate scenarios. The objectives of this thesis were (i) to develop a cassava simulation model that takes into account the effects of soil moisture and CO2 concentration on growth, development and tuber yield, and (ii) to simulate cassava yield in future climate scenarios for the Rio grande do Sul State. Model calibration was performed with data collected from experiments conducted in Santa Maria in crop year 2010-2011 and 2013-2014. The evaluation of themodel was performed with independent data from experiments conducted in Santa Maria during the 2011-2012, 2012-2013, 2013-2014 and 2014-2015 gowing seasons and with data collected in a commercial farm in Vera-Cruz during the 2013-2014 and 2014-2015 growing seasons. The two soil water balance models used were Thornthwaite and Mather model and the Ritchie model. The response function to CO2 was calibrated from free air CO2 enrichment experiments. A graphical interface was written in Java, and the source code was written in FORTRAN. The climate change scenarios used in this study are the scenario SRES A1B (Cmip3) of the 4th IPCC report and the RCP4.5 (Cmip5) of the 5th IPCC report. This study allowed the calibration of different processes of growth and development for cultivars Fepagro - RS 14, Estrangeira, Cascuda, São José e Paraguaia with no limitation by water. It was possible to include two soil water balance sub-models, and a CO2 response function that was incorporated into the Simanihot model to be used in climate change scenarios for the Rio Grande do Sul. A cassava simulator called Simanihot with all these simulation options was developed and made available at the official web site of the simulator (www.ufsm.br/simanihot). From the simulations wit the two future climate scenarios, the results show an increasing trend of cassava productivity for the state of Rio Grande do Sul of up to 30 t ha-1, depending on the cultivar, scenario and planting date. Increase trends in yield were smaller for the Cmip5 compared to the Cmip3 for the cultivar Estrangeira and the opposite for the cultivar Fepagro - RS 13. In the three analyzed future periods (2010-2039, 2040-2069 and 2070-2099), changes in yield were steadly, being the higherstin the last future period (2070-2099), and among the planting dates, always higher in dates of 01/09 and 01/10. The region of te Rio grande do Sul State with greater changes in tuber yield is the northeast reagion, where currently is the coldest region in the State.